Testing Broadcast Seeding Methods to Restore Urban Forests in the Presence of Seed Predators. Issue 6 (7th January 2013) - Overdyck, Elizabeth; Clarkson, Bruce D.; Laughlin, Daniel C.; Gemmill, Chrissen E. C.
Abstract Forest restoration in urban areas often occurs in isolation from remnant forest, limiting the chances for recolonization by native species. Plants with bird‐dispersed seeds can be particularly vulnerable to dispersal limitation and regeneration can be further impeded by non‐native seed predators. We used a factorial experiment to investigate broadcast seeding as a method to reintroduce trees with large seeds and fleshy fruits into early successional forests. We assessed rates of seed and fruit loss, germination and seedling establishment in three seed treatments: (1) caging to exclude introduced mammalian seed predators; (2) removal of fleshy fruit pericarp; and (3) placing seeds in nutritionally enriched clay balls. Across all species (Beilschmiedia tawa, Elaeocarpus dentatus, and Litsea calicaris) seeds and fruits accessible to mammalian predators suffered significantly greater loss (58%) than those protected by cages (4%). However, seed and fruit loss in the presence of predators was reduced to only 35% across all species by the treatment combining the removal of fruit flesh and clay ball application to seeds. Establishment of B. tawa seedlings after 1 year was significantly enhanced by the clay ball treatment (12% of seeds sown vs. 6% without clay balls). Very low establishment rates were recorded for E. dentatus and L. calicaris. Broadcast seeding was found to be a viable method of improving regeneration of large‐seeded late successional trees and may be a cost‐effective alternative to planting saplings. Seedling establishment can be improved with fruit flesh removal and clay ball treatments, especially in the presence of mammalian seed predators.